2021
DOI: 10.1038/s41598-021-98359-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-world gait speed estimation, frailty and handgrip strength: a cohort-based study

Abstract: Gait speed is a reliable outcome measure across multiple diagnoses, recognized as the 6th vital sign. The focus of the present study was on assessment of gait speed in long-term real-life settings with the aim to: (1) demonstrate feasibility in large cohort studies, using data recorded with a wrist-worn accelerometer device; (2) investigate whether the walking speed assessed in the real-world is consistent with expected trends, and associated with clinical scores such as frailty/handgrip strength. This cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…Nonetheless, when combined into a single, more robust endpoint, i.e., gait speed, it showed a decreasing trend toward frailty, and it resulted effective in distinguishing non-frail participants from both pre-frail and frail ones, confirming previous findings [38]. Also, the 95th percentile of gait speed, which estimates the upper-bound of the gait speed distribution, and hence it is more likely to reflect the physical reserve of the person, resulted significantly different across frailty groups, in agreement with previous findings [39].…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, when combined into a single, more robust endpoint, i.e., gait speed, it showed a decreasing trend toward frailty, and it resulted effective in distinguishing non-frail participants from both pre-frail and frail ones, confirming previous findings [38]. Also, the 95th percentile of gait speed, which estimates the upper-bound of the gait speed distribution, and hence it is more likely to reflect the physical reserve of the person, resulted significantly different across frailty groups, in agreement with previous findings [39].…”
Section: Discussionsupporting
confidence: 91%
“…These studies, which recruited participants from a cohort study involving community-dwelling older adults and measured DWS using a smartphone application or an accelerometer, could not include frail participants because the participants were required to go to the survey venue or designated location for collecting and uploading the data, which may be difficult for frail participants. Soltani et al 17 recently reported the discriminability of DWS for frailty; however, the frailty definition included only the body mass index and handgrip strength and was limited to weight loss and weakness.…”
Section: Introductionmentioning
confidence: 99%
“…In concert with the SDOC, we selected walking speed <0.8 m/s as the primary outcome for numerous reasons. First, walking speed has been recognized as the “6th vital sign” ( 39 ) and is an established predictor of adverse outcomes across adulthood ( 18 , 34 ). Second, in recognition of its clinical significance, walking speed <0.8 m/s has been consistently used as the cut point in recent sarcopenia definitions ( 40 ).…”
Section: Discussionmentioning
confidence: 99%